Synthesis of magnetic biochar using Bauhinia variegata leaves through one-pot hydrothermal process to degrade malachite green dye by Fenton-like catalysis - Ramesh Vinayagam; Gokulakrishnan Murugesan; Sujesh Sudarsan; Thivaharan Varadavenkatesan; Raja Selvaraj (PLoS ONE, 2026)
This study reports the facile one‑pot hydrothermal synthesis of a magnetite‑embedded magnetic biochar (Bv‑MBC) derived from Bauhinia variegata leaves and its application as a heterogeneous Fenton‑like catalyst for malachite green (MG) dye degradation. FESEM revealed a highly porous structure with uniformly distributed spherical iron oxide nanoparticles (mean size: 32.65 nm) embedded within the biochar matrix. BET analysis showed a specific surface area of 10.64 m 2 /g. XRD confirmed the presence of crystalline magnetite with an average crystallite size of 19.91 nm, along with an amorphous carbon signal. VSM measurements gave a saturation magnetization of 30.11 emu/g, sufficient to permit rapid magnetic collection of the catalyst after use. In batch trials, Bv-MBC acted as an efficient Fenton-like catalyst for MG, removing 75.01 ± 1.78% of the dye within 180 min at an initial concentration of 5 mg/L. The kinetic data were described by a second-order model, with the apparent rate constant falling from 0.0034 to 0.0003 L mg -1 min -1 as the starting MG concentration increased from 5 to 25 mg/L. The synthesized Bv‑MBC exhibited good stability, retaining 85.11% of its initial catalytic activity after five successive reuse cycles. The catalyst showed effective MG removal in multiple real water matrices, indicating potential applicability in complex aqueous environments. Hence, this study highlights a promising and easily separable magnetic catalyst to treat dye-contaminated wastewater.